Hubungan Mutu Pelayanan Kesehatan dengan Kepuasan Pasien di Rumah Sakit Umum Daerah Kabupaten Buton Utara - Rizki, Sartini; Rasmiani, Rasmiani (Jurnal Gizi Ilmiah, 2016)
The problem at the North Buton District Hospital is that there are patient complaints, where the officers are not friendly in communicating both to patients and the patient's family and the officer's inaccuracy in fulfilling his appointments with patients. This study aims to determine the relationship between the quality of health services and patient satisfaction in North Buton District Hospital. This type of research is analytic with a cross sectional approach. The population in this study were all inpatients at the North Buton District Hospital and used hospital services from January to April 2016 with a total of 108 patients with a total sample of 44 respondents who were determined by accidental sampling. The analysis used is univariate and bivariate analysis. The results of the study concluded that there was a significant relationship between responsiveness, assurance, empathy, reliability, and tangibles with patient satisfaction at the North Buton District Hospital. It is recommended for the Health Office to include physical development and the addition of human resources as auxiliary personnel, especially in North Buton District Hospital in the priority planning proposals to the North Buton Regency government, as well as carry out education or training for medical and paramedical personnel on a regular, periodic and comprehensive basis in order to improve professional skills and performance. In addition, there is a need to improve the quality of hospital physical evidence, reliability and the provision of better health insurance